Quarterly report on the prices of selected commodities in some towns of Bauchi State : October - December of 1979 - Nigeria. Bauchi State; Ministry of Economic Planning, Statistics Unit. (Bauchi : Ministry of Economic Planning, Statistics Unit, 1979)
This is a quarterly report on the prices of selected commodities in some towns, Bauchi State of Nigeria, October - December of 1979, prepared by the Ministry of Economic Planning, Statistics Unit.
lje 05/03/2019
Arch.
Keywords: Food prices; Bauchi State